Associated Risk Factors among the Type 2 Diabetes Patients Attended at Chattogram Diabetic General Hospital - Moitree Biswas; Mohammad Alamgir Hossain; Towhida Kamal; Asma Mostafa; Md Ibrahim Sohel (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Diabetes Mellitus (DM) is a metabolic illness characterized by hyperglycemia due to inadequate insulin synthesis by pancreatic beta (b) cell or insulin resistance. Awareness of associated risk factors of Type 2 Diabetes Mellitus (T2DM) can decrease complications as well as mortality. The present study was done to describe the associated risk factors among the T2DM patients attended at a tertiary care hospital. Materials and methods: A descriptive study was conducted at Chattogram Diabetic General Hospital from December 2021 to June 2022.A total of 400 diabetic respondents, aged 45-90 years, were recorded. Data regarding associated risk factors were collected by using a pretested, semi-structured questionnaire. Statistical analysis was done using SPSS (Statistical Package for Social Science) version 20. Results: Results demonstrate that, 45-55 years age group was more affected (62.3%) and positive family history also shown more occurrence of T2DM in female (55.8%). Majority of the female participants without physical activity (43.3%) were diagnosed T2DM and also observed that the female who intake more carbohydrate (40.5%) and being overweight were identified as T2DM. Conclusions: By modifying lifestyle (Less carbohydrate intake, weight reduction and more physical activity) the occurrence of T2DM might be reduced. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 69-72